Biosynthesis of Camalexin from Tryptophan Pathway Intermediates in Cell-Suspension Cultures of Arabidopsis - Zook, Michael (American Society of Plant Physiologists, 1998)
Camalexin (3-thiazol-2′-yl-indole) is the principal phytoalexin that accumulates in Arabidopsis after infection by fungi or bacteria. Camalexin accumulation was detectable in Arabidopsis cell-suspension cultures 3 to 5 h after inoculation with Cochliobolus carbonum (Race 1), and then increased rapidly from 7 to 24 h after inoculation. Levels of radioactivity incorporated into camalexin during a 1.5-h pulse labeling with [(14)C]anthranilate also increased with time after fungal inoculation. The levels of radioactive incorporation into camalexin increased rapidly between 7 and 18 h after inoculation, and then decreased along with camalexin accumulation. Relatively low levels of radioactivity from [(14)C]anthranilate incorporated into camalexin in the noninoculated controls. Autoradiographic analysis of the accumulation of chloroform-extractable metabolites labeled with [(14)C]anthranilate revealed a transient increase in the incorporation of radioactivity into indole in fungus-inoculated Arabidopsis cell cultures. The time-course measurement of radioactive incorporation into camalexin during a 1.5-h pulse labeling with [(14)C]indole was similar to that with [(14)C]anthranilate. These data suggest that indole destined for camalexin synthesis is produced by a separate enzymatic reaction that does not involve tryptophan synthase.